Negotiating Success - Jim Hornickel (Wiley, 2014)
"Negotiating Success is an inspiring book that skillfullyintegrates the hard and soft skills needed to ensure win-winoutcomes in negotiations. The reader will raise his/her emotionalintelligence, learn new concepts based on the latest brainresearch, understand the principles of ethical influence, and gainthe skills and steps necessary for intelligent negotiations. Hardskills with soft edges—that's the winning formula!"